Association between Salivary Factors and Growth of Cariogenic Bacteria in Type-2 Diabetes Mellitus - Mustakim, Ahmed; Datta, Suvamoy; Rahman, Kazi Billur; Hamid, KR Reaz (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Dental caries is a chronic infectious disease involving the destruction of dental hard tissues by lactic acid, primarily initiated by Streptococcus mutans and progressed by Lactobacilli. In patients with Type-2 Diabetes Mellitus (T2DM), factors such as poor glycemic control and altered salivary properties are linked to increased caries risk. This study aimed to evaluate the association between salivary factors, glycemic status, and the growth of cariogenic bacteria in T2DM patients. Methods: This cross-sectional analytical study included 108 T2DM patients (aged >30 years, diagnosed for ≥ 1 year) recruited from the Outpatient Department of Dentistry, National Healthcare Network (NHN), Wari under the Diabetic Association of Bangladesh, Dhaka. While exposure variables included salivary pH, glucose, flow rate, and saliva buffering capacity, outcome variables were the type and load of cariogenic bacteria (High load: ≥ 105 CFU/ml, and Low load: <105 CFU/ml). Uncontrolled diabetes was defined as HbA1c ≥ 6.5%. Salivary flow was categorized as normal flow rate (>1 g/min), moderately low flow rate (0.7-1 g/min) and very low flow rate (< 0.7 g/min), and buffering capacity was determined by comparing the color of the test field with that of the sample as blue, green and yellow colors indicating high, moderate and low buffering capacity respectively. Results: Neither age nor sex showed a significant association with bacterial load. However, elevated Fasting Blood Sugar (FBS) significantly increased the risk of a high bacterial load (OR: 6.4, 95% CI: 2.4–17.2, p < 0.001). Uncontrolled diabetes was associated with a nearly 12-fold higher risk of significant cariogenic bacterial load compared to controlled cases (OR: 11.7, 95% CI: 3.6–38.1, p < 0.001). Xerostomia also showed a strong correlation with high bacterial load (OR: 6.0, 95% CI: 2.1–16.8, p < 0.001). Furthermore, low salivary pH, elevated salivary glucose, very low salivary flow rate (found in 47.6% of high-load cases), and low-to-moderate buffering capacity (found in 90.5% of high-load cases) were all significantly associated with increased bacterial growth (p < 0.001). Conclusion: Elevated FBS, uncontrolled glycemic status, and xerostomia are major drivers of high cariogenic bacterial loads in T2DM patients. Additionally, physiological changes in saliva-specifically reduced pH, increased glucose levels, low flow rates, and diminished buffering capacity-significantly promote the proliferation of Streptococcus mutans and Lactobacilli. These findings emphasize the importance of integrated oral health monitoring and strict glycemic management to mitigate caries risk in diabetic populations Ibrahim Cad Med J 2025, 15(1): 13-20